KAJIAN FUNGSI EKOLOGIS DAN ESTETIS RUANG TERBUKA HIJAU DI KAWASAN RAWAN BANJIR : Studi Kasus RTH Kawasan Pasar Segiri, Sub DAS Karang Mumus, Kota Samarinda - Dharwati P. Sari (Jurnal Arsitektur ZONASI, 2022)
The Karang Mumus sub-watershed around the Segiri market in Samarinda, east Kalimantan is a startegic area in city. Not only having economic value but also this area has an important role to maintain environmental quality. Frequent flooding in Samarinda is caused by many factors, such as the lack of availability of infiltartion. The Green Open Space (RTH) in Karang Mumus sub-watershed around the Segiri Market is very useful for cathed the rain water. Environmental engineering in green open space can be an alternative to flood control facility. Some of the engineering carried out in the Karang Mumus sub-watershed has an impact on visual quality and benefits for community social activities.This research is hoped this environmentak engineering will also provide ecological benefits, especially reducing the risk of flooding.Keywords: Green open space; watershed, Flood